EFEKTIFITAS SISTEM REKAM MEDISDENGAN MENGGUNAKAN UNIT NUMBERINGSYSTEM (UNS) DI KLINIK UTAMA RAWAT INAPPKU MUHAMMADIYAH KUTOARJO (STIE Rajawali Purworejo, 2018)
Hospital medical record is an important component in the implementation of hospital management activities, hospital medical records must be able to provide complete information about the medical and health services process at the hospital,both in the past, present and future estimates of what will happen. The purpose of the medical record is to support the achievement of orderly administration in order to improve health services. Without the support of a good medical record management system, then the orderly administration will not succeed. Medical records arevery supportive not only to organize important instrument processes in handling medical legal problems that may occur in hospitals less successfully in aneffort to improve the quality of service as expected.The most important thing in the medical record is the numbering of medical record documents. One type of medical record numbering used is the Numbering System Unit (UNS) is a numbering system where the system provides one number to outpatients, inpatient and emergency department. Each visiting patient receives one number when the patient first arrives to the hospital and is used forever on subsequent visits. The patient's medical record number is unlikely to be used for the number of another patient, since the numbering is already organized and will be continuous with the filling of the medical record document and in the process of handling the patient. Based on research conducted in Main Clinic of Inpatient PKU Muhammadiyah Kutoarjo in giving medical record number Unit Numbering System (UNS) have been run well and effective start from place of registration of patient, filling of medical record by doctor, giving medicine to patient, with ease in searching, storing, and maintaining patient's medical record but still experiencing the problem of duplicate nu mbering at the time of patient registration where the patient got double number, although not nearly every day found the existence of double patient medical record number.